(3GdJbGQjQ GdeGdjI (B:s (3CSS GdEYOGO hGdYQV hGdJMdjd habG dCMOK GdEUOGQGJ hGdJYOjdGJ aj eYGjjQ GdeMGSHI GdOhdjI hGdCeQjcjI hGdHQjWGfjI hGdYQHjI hGdeUQjI (B/s - (3MeGO, WGQb YHO GdYGds ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2002)
(3ebOeI Yf GdeYGjjQ GdeMGSHjI(B-(3EWGQ EYOGO hYQV GdbhGFe GdeGdjI habG ddeYGjjQ GdeMGSHjI GdCeQjcjI hGdOhdjI hGdHQjWGfjI(B-(3CSS EYOGO hYQV GdbhGFe GdeGdjI GdCSGSjI(B-(3EYOGO hGSJNOGe bGFeI GdJOabGJ GdfbOjI(B- (3fUjH GdSge GdhGMO ef GdCQHGM aj VhA GdeYGjjQ GdeMGSHjI(B- (3UGaj QHM Ch NSGQI GdaJQI hGdCNWGA GdLhgQjI hJZjjQ GdSjGSGJ GdeMGSHjI(B-(3GdJbGQjQ GdeGdjI GdeQMdjI(B- (3GdJbGQjQ GdbWGYjI habG ddeYGjjQ GdeMGSHjI(B-(3JMdjd GdbhGFe GdeGdjIs
(3HjHdjhZQGajG(B: (3U(B.631-632s
Keywords: (3GdeGdjI GdYGeIs; (3eMGSHIs